2021
DOI: 10.3390/electronics10182184
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Analysis of a Compact Quad-Element UWB MIMO Antenna for Automotive Communications

Abstract: This paper presents the design and analysis of a planar ultra-wideband (UWB) multiple-input-multiple-output (MIMO) antenna for modern vehicular communication systems. The proposed unit cell antenna structure was designed using modified elliptical radiators on a Rogers RO3003 substrate, has a size of 22 × 22 × 0.76 mm3, and covers an impedance bandwidth (S11 ≤ −10 dB) of 3.14 GHz to 12.24 GHz. The peak gain and efficiency of the unit cell prototype are 5.1 dBi and 81%, respectively. The unit cell was further de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Studies carried out in recent years [35][36][37][38]52,53] reported that machine learning classification algorithms distinguish suspicious from non-suspicious skin lesions. These studies are geared towards the development of automated diagnosis systems, but the presence of the anisotropy of the images makes the automated analysis of dermatological images a difficult task [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in recent years [35][36][37][38]52,53] reported that machine learning classification algorithms distinguish suspicious from non-suspicious skin lesions. These studies are geared towards the development of automated diagnosis systems, but the presence of the anisotropy of the images makes the automated analysis of dermatological images a difficult task [40].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the examples mentioned above, fractal analysis can be using wide industrial applications, i.e., in civil engineering [29,30], material science [31,32], geology [33,34], chemical sciences [35,36] and automotive [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The corporate-fed array illustrated in [14] would occupy a larger physical footprint, when designed for the 28 GHz band. The MIMO concept illustrated in [15] might not be scaled down to Ka band. However, the design and deployment of phased arrays would be expensive.…”
Section: Proposed Pattern Diversity Antennamentioning
confidence: 99%
“…1. The proposed antenna covers multiple bands, including UWB, whereas other antennas reported in the literature [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] operate on a single wideband frequency. 2.…”
Section: On-car Scenariomentioning
confidence: 99%
“…2. The proposed antenna requires less space than the antenna configurations reported in [39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55]. 3.…”
Section: On-car Scenariomentioning
confidence: 99%